THE ROLE OF LABOR IN MEDIATING THE EFFECT OF WAGES, INVESTMENT, EDUCATION AND HEALTH ON GROSS REGIONAL DOMESTIC PRODUCT IN INDONESIA - Aini Rahma; Sirojuzilam; M. Syafii (RADJA PUBLIKA, 2026)
Equitable and sustainable economic growth has become an important agenda in Indonesia’s development, especially through the strengthening of the Gross Regional Domestic Product (GRDP). Labor is a main production factor that is suspected to play a mediating role in channeling the influence of various economic determinants on regional performance. This study aims to analyze the role of labor (LFPR) in mediating the influence of wages, domestic investment (PMDN), education, and health on GRDP in 34 provinces in Indonesia during the 2014–2023 period. The analysis was carried out using panel data with a path analysis approach and mediation testing using the Sobel Test. The results of the study show that directly wages, education, health, and investment have a significant effect on GRDP, while the influence of these variables on LFPR shows variations in significance. Indirectly, only wages and education are proven to have a significant effect on GRDP through LFPR as a mediating variable, while investment and health do not show significant mediation effects. These findings emphasize that improving the quality and involvement of labor is an important channel in transmitting the economic impact of wage and education improvements, while the influence of investment and health works more dominantly through direct mechanisms on economic output. This study contributes to strengthening the literature on human-capital-based development and provides more directed policy guidance in encouraging inclusive and sustainable regional economic growth.